Range selection and predecessor queries in data aware space and time - Oguzhan Külekci, M.; Thankachan, Sharma V. (Elsevier BV, 2017)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Predecessor search; Range searching; Data structures; Analysis of algorithms and problem complexity; predecessor search; data structures; Data compression; range searching; Coding and information theory (compaction, compression, models of communication, encoding schemes, etc.) (aspects in computer science); Searching and sorting; data compression